(untitled) (Eurasian Medical Research Periodical, 2022)
This research was in Laboratory No. 3 in the Department of Life Sciences / College of Education for Pure Sciences at Wasit University to track the development of the blood vessels of chicken embryos in different growth periods as well as to study the rates of egg weights of different ages and this research included chicken embryos due to the ease of access and ease of entry and follow-up. Persistent . Where the samples (eggs) were collected 150 locally fertilized eggs from Al-Kut market and placed in the incubator at a temperature of 37 ° for a period of 14 days and weighed during the first day and examined by a photodetector, then the samples were divided into three groups for the purpose of histological study, knowledge of changes and follow-up of embryonic development According to the way the dye works (Hematoxlyn-Eosin .) And through the study of the histological sections, it became clear that the blood vessels at the beginning of their development appear in the form of blood islands and then develop into a blood vessel whose wall consists of one region of cells in the wings of the mesoderm at the stage of 24-22 incubation hours. Part of the opaque area near the transparent area was observed. It is more opaque and has a speckled appearance due to the invasion of the lateral mesoderm as a result of its peripheral growth and access to it. As for the endoderm, its cells have its peripheral part adherent to the yolk, and this part of the yard is called the vascular area, which suffers a rapid expansion, is in the form of a blood network on the seventh day and then this network connects with each other To form a blood circulation (outgoing and afferent). On day 14, the vitelline blood vessel appears in a large and clear way, and the vitelline vein is observed, due to the increased consumption of the fetus In terms of studying the averages, egg weights during the first and second week, the weight loss of those eggs is observed during this period and is consistent with the development of blood vessels, and it may be the reason for the loss of egg weight with the effect of temperature on the egg and the growth of the fetus inside the egg.